Defending Women's Rights in Europe : Gender Equality and EU Enlargement - Avdeyeva, Olga A., 1976- (Book collections on Project MUSE., 2015)
Between 2004 and 2007, ten post-communist Eastern European states became members of the European Union (EU). To do so, these nations had to meet certain EU accession requirements, including antidiscrimination reforms. While attaining EU membership was an incredible achievement, many scholars and experts doubted the sustainability of accession-linked reforms. Would these nations comply with EU directives on gender equality? To explore this question, Defending Women's Rights in Europe presents a unique analysis of detailed original comparative data on state compliance with EU gender equality requirements. It features a comprehensive quantitative analysis combined with rigorous insightful case studies of reforms in Poland, the Czech Republic, and Lithuania. Olga A. Avdeyeva reveals that policy and institutional reforms developed furthest in those states where women's advocacy NGOs managed to form coalitions with governing political parties. After becoming members of the EU, the governments did not abolish these policies and institutions despite the costs and lack of popular support. Reputational concerns prevented state elites from policy dismantling, but gender equality policies and institutions became marginalized on the state agenda after accession. -- Amazon.com.